ASEAN-5 Passenger Car Industry Outlook: The Driving Forces, Opportunities and Challenges - Quek, Wu Kheng (2010)
Global automotive industry is growing at an unprecedented speed in the past decade, primarily due to the strong and fastest growing demand from the Asian emerging economies. ASEAN-5 is an economic block with huge potential. It is an attractive alternative destination for business compare with other emerging economies. Total population is 420 million people and combined economic size of $1,355 billion in this region. ASEAN-5 countries are one of the major driving markets contributed to the rapid growth of Asian automotive industry. This management project provides an outlook of the ASEAN-5 passenger car market and explores the driving forces, opportunities and challenges faced by the industry.